The Effect of Boiling Time of Wulung Bamboo Fiber (Gigantochloa Atroviolacea) in NaOH Solution on Tensile Strength of Epoxy Matriced Composites - Bintarto, Redi; Widodo, Teguh Dwi; Raharjo, Rudianto; Sulistyo, Erwin; Tamtomo, Bagas (International Journal of Mechanical Engineering Technologies and Applications, 2022)
The purpose of this study was to determine the effect of immersion time of NaOH at a temperature of 60-70 â„ƒ in wulung bamboo fibers on the tensile strength of the epoxy matrix composites. Wulung bamboo fibers (Gigantichloa Atroviolacea) have the potential to be used as reinforced in composites because they have high strength and are widely grown in Indonesia. In this study, bamboo wulung fiber reinforcement was used without treatment and with variations, soaking time 30 minutes, 60 minutes, and 90 minutes in 6% NaOH solution with a temperature of 60-70 â„ƒ. The composite manufacturing method used was vacuum assisted resin infusion and the standard composite specimen used as a tensile test was ASTM D638-01. The results showed that the longer the immersion time resulted in a rougher topography of the fiber surface which caused the composite tensile strength to increase due to the better mechanical interlocking between the fibers and the epoxy resin matrix. The wettability results on the fibers also show that the wetness between the fibers and the epoxy resin matrix is getting better, which is shown from the droplet contact angle on the resulting fibers. The highest composite tensile strength was obtained at 90 minutes immersion time of 169.765 MPa followed by immersion time of 60 minutes of 123.2 MPa, immersion time of 5 minutes of 81.7 MPa and without treatment of 71.6 MPa. Based on the results of the macro photo shows that the treatment given will reduce the failure of the pull out and debonding defects on the composite fracture.